PERENCANAAN KEBIJAKAN BERBASIS NILAI DAN PARTISIPATIF DI PESANTREN MODERN AL-HUDA AL-MUSRI’1: PERENCANAAN KEBIJAKAN BERBASIS NILAI DAN PARTISIPATIF DI PESANTREN MODERN AL-HUDA AL-MUSRI’1 - Afif Sirojul Munir; Fauzi, Rizal (Perkumpulan Peneliti dan Pegiat Literasi, 2026)
The gap in faith-based educational management research remains largely descriptive and has yet to operationally construct a value-based policy model within a policy cycle framework. This study aims to construct a conceptual model of value-driven policy governance at Pesantren Modern Al-Huda Al-Musri'1. A qualitative case study approach was employed, utilizing in-depth interviews, observations, and document analysis involving nine key informants consisting of the foundation chairman, kiai council members, senior teachers, and administrative staff. The findings indicate that the policy process operates in a circular cycle consisting of three stages: value-embedded deliberative planning through kiai deliberation forums, integrative implementation combining traditional bandongan and sorogan methods with digital innovation, and reflective evaluation through the Temu Keluarga forum. Based on these findings, the study constructs the Value-Driven Participatory Policy Cycle as a conceptual model explaining how spiritual values function as institutional infrastructure in faith-based educational governance, where policy legitimacy is built through collective moral consensus rather than formal authority alone.